Recombinant Leishmania-activated C kinase as a novel antigenic candidate for immuno-diagnosis of visceral leishmaniasis occurring in India and Brazil - Anirban Bhattacharyya; Nicky Didwania; Sarfaraz Ahmad Ejazi; Rudra Chhajer; Saswati Gayen; Mehebubar Rahman; Rama Prosad Goswami; Krishna Pandey; Vidya Nand Ravi Das; Pradeep Das; Fernando Oliveira da Silva; Dorcas Lamounier Costa; et al. (Infectious Diseases of Poverty)
Abstract Background Visceral leishmaniasis (VL) an ‘infectious disease of poverty’, caused by the Leishmania donovani complex, remains a significant public health threat in endemic regions of South Asia, East Africa, and Brazil. Early and accurate diagnosis is critical to prevent the disease's potentially fatal outcomes. However, due to the nonspecific nature of clinical symptoms, diagnosis often relies on serological tests. This study aims to assess the diagnostic potential of the L. donovani activated C kinase (LACK), a highly conserved antigen essential for parasite survival and host establishment, in VL-endemic regions such as India and Brazil. Methods We conducted a multi-center study with serum samples from India (n = 184) and Brazil (n = 59), along with non-invasive urine samples from India (n = 132). Clinical samples from India were collected from the endemic regions of Bihar and West Bengal between 2016–2024, while those from Teresina, Brazil, were collected between 2008 and 2009. Following preliminary immunoblot analysis, we validated the diagnostic utility of LACK through enzyme-linked immunosorbent assays (ELISA) and dipstick tests. Results were analyzed and area under a Receiver Operating Characteristic (ROC) curve (AUC) values were calculated via the Mann–Whitney U test. Additionally, sensitivity, specificity, and confidence intervals were assessed to evaluate diagnostic performance. Results The ELISA results revealed that LACK antibodies exhibited 100% sensitivity in both Indian [95% confidence intervals (CI): 94.80–100%] and Brazilian (95% CI: 91.24–100%) patient samples, with specificity of 97.33% for Indian controls and 94.74% for Brazilian controls. Urine samples from Indian patients also demonstrated perfect sensitivity and specificity (100%). Notably, LACK showed minimal reactivity with follow-up patient samples. Dipstick assays confirmed these findings, offering a simple, rapid, and field-friendly diagnostic alternative. Conclusion LACK is a promising diagnostic marker for VL, showing high sensitivity across regions and has potential to distinguish active infections from cured or relapsed cases, though larger studies are needed for confirmation. Graphical Abstract